PENERAPAN MEDIA MINI SOCCER BALL TERHADAP PEMBELAJARAN SEPAK SILA PADA SEPAK TAKRAW SISWA KELAS V SD NEGERI KETABANG SURABAYA - CHRISWANTO, MOCHAMMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Teacher should be able to create a learning model which is appropriate to the students’ characteristic that is taught by decreasing or increasing the complexity and difficulty level of the learning task by modifying the equipment or the infrastructure. When it is about the equipment or the infrastructure, then it is also about the learning media. Because a learning media has a function to present the message or learning material with the equipment or the infrastructure. If the teacher is able to implement or apply the learning model with the media, hopefully it can overcome the difficulties in accomplishing sepak sila technique of sepak takraw, one of the ways is by modifying takraw ball into mini soccer ball media. The objective of this research is to know the influence and the rate of the influence of the implementation of mini soccer ball media to sepak sila learning for the fifth grade students of SD Negeri Ketabang Surabaya. The total population is 140 from the fourth grade which will be performed cluster sampling to be in a group or will be take from the whole one class, then it will be used as the sample which has 35 students in total. Based on the hypothesize test from t-test calculation result by using SPSS 17.0 application its obtained t-count result as big as 9,891 and t-table as big as 2,0315. Since t-count is bigger than t-table, thus there is significant difference between sepak sila test result on sepak takraw of fifth grade students of SD Negeri Ketabang Surabaya before and after receiving the treatment by implementing the mini soccer ball media. From the calculation, it can be concluded that the implementation of mini soccer ball media has given effect to sepak sila learning of sepak takraw for fifth grade students of SD Negeri Ketabang Surabaya. Along with the rate of the influence of  mini soccer ball media implementation to sepak sila learning of sepak takraw for the fifth grade students of SD Negeri Ketabang Surabaya is 23,18%. Keywords:  Modification, media.